The Role of Investment Motivation in Financial Literacy and Women's Behavior - Marpaung, Arif Pratama; Muhammad, Idhamsyah; Hamdani, Rizki; Hafiz, Muhammad Shareza; Sani, Agus (Politeknik Negeri Batam, 2024)
This study explores how financial literacy, financial education, and self-control affect investment motivation and financial behavior among women in Medan, Indonesia. A total of 270 participants responded to a structured questionnaire, distributed three times from February to June 2024, covering five key areas: financial behavior, investment motivation, financial literacy, financial education, and self-control. Using Partial Least Squares Structural Equation Modeling (PLS-SEM) for analysis, the findings reveal that both financial literacy and education significantly enhance investment motivation and financial behavior. Higher education levels correlate with better financial literacy, resulting in more strategic investment decisions. Although many respondents allocate a significant portion of their income to monthly expenses, those with higher financial literacy manage their finances more effectively. However, the study finds no significant impact of self-control on investment motivation and financial behavior, possibly due to the respondents' younger age and lower income. This research underscores the importance of financial literacy and education in shaping financial behavior.